Data Security Analysis Against Chosen Ciphertext Secure Public Key Attack Using Threshold Encryption Scheme - Khairunas Khairunas; Muhammad Zarlis; Sawaluddin Sawaluddin (RIRAI Publisher, 2021)
A public key encryption cryptography system can be utilized to generate ciphertext of a message using a public key. However, this public key encryption cryptography system cannot be utilized if you want to generate ciphertext using several different keys. Solving the problems above can use the Chosen Ciphertext Secure Public Key Threshold Encryption scheme but are the securities from Threshold Encryption really strong in securing messages, therefore the above problems can be analyzed for Data Security Against Chosen Ciphertext Secure Public Key Attacks Using Threshold Encryption Schemes. The work process starts from Setup which functions to generate the server's private key and public key. Then, the process is continued with ShareKeyGen which functions to generate private keys based on the user's identity. After that, the process continues with ShareVerify which serves to verify the key generated from the ShareKeyGen process. The process will be continued again with Combine which serves to generate a private key that will be used in the decryption process. After that, the process will continue with the encryption process of the secret message. The ciphertext obtained will be sent to the recipient. The receiver verifies the ciphertext by running ValidateCT. Finally, the ciphertext is decrypted by running Decrypt. The software created can be used to display the workflow process of the Threshold schema. In addition, it makes it easier to test intercepts of ciphertext messages to other users so that generic securities analysis is carried out in testing the resulting ciphertext. The results of the implementation of Threshold Encryption algorithm scheme can protect important personal data, because it involves human rights, namely the right to access, the right to delete, the right to correct, the right to be corrected and the right to transfer personal data safely from attacks.